Radical Titanocene Promoted Coupling of Epoxides and Vinyl Sulfones. Issue 3 (4th December 2014) - Fernández‐Mateos, Alfonso; Encinas‐Madrazo, Soledad; Herrero‐Teijón, Pablo; Rubio González, Rosa
Abstract: A radical coupling reaction of diverse vinyl sulfones and epoxides was mediated by Cp2 TiCl (Cp = cyclopentadienyl) to provide a straightforward synthetic pathway to hydroxy sulfones. The reaction was successfully achieved by using either an excess or a catalytic amount of the Ti III reagent. The scope of the reaction was studied for several different functionalized and substituted epoxides and vinyl sulfones. Abstract : A radical coupling reaction of vinyl sulfones and epoxides was mediated by Cp2 TiCl (Cp = cyclopentadienyl) to provide straightforward synthetic access to hydroxy sulfones. The reaction was achieved by using either an excess or a catalytic amount of the Ti III reagent. The scope of the reaction was studied for several different substituted epoxides and vinyl sulfones.